Combined Alkali‐Organoammonium Structure Direction of High‐Charge‐Density Heteroatom‐Containing Aluminophosphate Molecular Sieves. (27th May 2019) - Seo, Seungwan; Ahn, Nak Ho; Lee, Jeong Hwan; Knight, Lisa M.; Moscoso, Jaime G.; Sinkler, Wharton A.; Prabhakar, Sesh; Nicholas, Christopher P.; Hong, Suk Bong; Lewis, Gregory J.
Abstract: The charge density mismatch concept was applied to the synthesis of high‐charge‐density silicoaluminophosphate SAPO‐69 (OFF) and SAPO‐79 (ERI) and zincoaluminophosphate PST‐16 (CGS), PST‐17 (BPH), PST‐19 (SBS), and ZnAPO‐88 (MER) molecular sieves. Combined alkali‐organoammonium structure direction in these systems is thus enabled. Structure direction is treated from the perspective of stabilizing an ionic framework, the relationships between reaction charge density (OH − /H3 PO4 ), alkali and organoammonium content, and ionicity of tetrahedral framework atoms in successful structure direction are presented. Abstract : Sechs mal sieben : Die Einführung einer kombinierten Alkalimetall‐Organoammonium‐Strukturlenkung eröffnet den Zugang zu molekularen ZnAPO‐ und SAPO‐Sieben mit hoher Ladungsdichte, darunter PST‐16 (CGS), PST‐17 (BPH), PST‐19 (SBS), ZnAPO‐88 (MER), SAPO‐69 (OFF) und SAPO‐79 (ERI).